Implementasi Corporate Social Responsibility PLTU Jateng 2 Adipala Cilacap Pada Kelompok Batik Seloka - Ayu Widyaningrum; Taufik Hidayanto; Galih Eka Purnomo (Politeknik Negeri Cilacap, 2023)
Indonesian batik is highly diverse and unique, reflecting the cultural diversity and history of the Indonesian nation. Batik also holds symbolic meanings and is often used in special events, ceremonies, and cultural celebrations. Kelompok Batik Seloka is a local batik artisan community located around the operational area of PLTU Jateng 2 Adipala Cilacap. As part of the local community, this batik group strives to preserve the cultural heritage of batik and develop their business in this field. PLTU Jateng 2 Adipala Cilacap, as part of its social responsibility, has formed a partnership with Kelompok Batik Seloka to provide support and assistance in various forms through the Corporate Social Responsibility (CSR) program. This program aims to develop skills and knowledge among the community members to drive regional economic development. The community engagement aims to enhance the skills and knowledge of Kelompok Batik Seloka, implemented by the Community Development Program Team of PT. Indonesia Power PLTU Jateng 2 Adipala Cilacap. Several activities have been conducted in this community engagement, such as Batik Dye Usage Training, Motif Making Training, Digital Marketing Training, and Eco-printing Training. The results of this community engagement show that Kelompok Batik Seloka has acquired more skills to create various types of batik, with the hope of becoming more self-sufficient in increasing their production output and ultimately improving the welfare of the community in Adipala District.